Visualization analysis of research on executive function in overweight or obesity - Li Zhanquan; Chen Zekai; Zhu Lin; Liu Fuxian (Sichuan jingshen weisheng, 2022)
ObjectiveTo study the current status and development trend of research on the executive function in overweight or obesity， and to grasp the research hotspots in this field.MethodsA total of 1 321 literatures relevant to the executive function in overweight or obesity collected in Web of Science Core Collection database from 2010 to 2021 were selected. CiteSpace and VOSviewer were used to generate knowledge graphs for visualization analysis， then the number of articles issued， countries/regions， institutions and the co-occurrence， clustering and burst of keywords were analyzed.Results①In terms of the trend of the number of articles issued from 2010 to 2021， the annual quantity of published articles about the executive function in overweight or obesity presented a rapid growth over 2010-2014， then entered into a slow growth stage over 2014-2017， and emerged a rapid growth over 2017-2021. ②From the perspective of countries / regions， a total of 64 countries and regions participated in the research. The largest number of articles issued in this field was the USA， which had the most frequent cooperation and exchanges with other countries and regions， and exerted the greatest academic influence， occupying the core position of this research field. ③From the perspective of research institutions， a total of 1 627 institutions participated in this research field， among which the Illinois University published the most papers and closely cooperated with many productive institutions， forming a research group with a certain scale. ④From the perspective of keywords， the research content mainly involved dietary behavior research， prevention and intervention research， risk factor assessment， and analysis of the characteristics of different groups.ConclusionResearches on executive function in overweight or obesity have been developing rapidly， attracting international attention and covering a wide range of areas.